Mapping the Evolution of Sustainability Reporting Determinants: A Systematic Literature Review Across Organizational Capabilities and Institutional Pressures - Wilda Anabia Prasasti; Christian Halomoan Hasibuan; Iskandar Muda (Indonesia Economic Journal, 2025)
Sustainability reporting has become a strategic corporate practice that reshapes how organizations communicate environmental, social, and governance information to stakeholders. This study examines the determinants of sustainability reporting adoption and quality through a systematic literature review (SLR) of peer-reviewed studies (2023-2025). Drawing on Scopus-indexed articles selected in the PRISMA process, the review synthesizes key findings using a multi-theoretical framework and determinants of sustainability reporting. The results show that sustainability reporting is jointly shaped by internal organizational capabilities, such as corporate governance, leadership orientation, firm size, sector, profitability, and human capital, and external institutional pressures including regulation, capital markets, non-governmental organizations, socio-cultural norms, and technological systems. While institutional pressures expand disclosure, reporting quality depends critically on internal capabilities, with weak alignment leading to symbolic adoption. The study contributes a concise integrative framework to explain variations in sustainability reporting quality and identifies a structured agenda for future empirical research.